2023
DOI: 10.1371/journal.pone.0282007
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral brain-derived neurotrophic factor (BDNF) and salivary cortisol levels in college students with different levels of academic stress. Study protocol

Abstract: Introduction Brain-derived neurotrophic factor (BDNF) is essential for brain physiological processes influencing memory and learning. BDNF levels can be affected by many factors, including stress. Stress increase serum and salivary cortisol levels. Academic stress is of the chronic type. BDNF levels can be measure from serum, plasma or platelets, and there is still no standard methodology, which is relevant to ensure reproducibility and comparability between studies. Hypothesis (i) BDNF concentrations in ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…To our knowledge, the present study is the first that evaluated and compared the amount of two circulating components of the neurotrophin BDNF, the platelet-poor plasmatic (PPP-BDNF) and the intraplatelet (PLT-BDNF) pools, in a group of patients with a lifetime diagnosis of bipolar disorder, distinguished with respect to the presence of current post-traumatic symptoms or depressive episodes, and a group of healthy controls without somatic or mental diseases. Essentially, these two BDNF circulating parameters were evaluated as presumed biomarkers of the activity of the CNS periphery communication networks involving the neurotrophin system in these groups of enrolled subjects [ 35 , 36 , 41 , 42 , 65 , 66 ]. First, results showed that the two BDNF parameters were not significantly correlated to each other, in support of their distinct origin [ 29 , 43 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the present study is the first that evaluated and compared the amount of two circulating components of the neurotrophin BDNF, the platelet-poor plasmatic (PPP-BDNF) and the intraplatelet (PLT-BDNF) pools, in a group of patients with a lifetime diagnosis of bipolar disorder, distinguished with respect to the presence of current post-traumatic symptoms or depressive episodes, and a group of healthy controls without somatic or mental diseases. Essentially, these two BDNF circulating parameters were evaluated as presumed biomarkers of the activity of the CNS periphery communication networks involving the neurotrophin system in these groups of enrolled subjects [ 35 , 36 , 41 , 42 , 65 , 66 ]. First, results showed that the two BDNF parameters were not significantly correlated to each other, in support of their distinct origin [ 29 , 43 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have observed a decrease in plasma and serum BDNF levels in patients with depression (Polyakova et al., 2015 ; Yoshimura et al., 2007 ), bipolar disorder (Cunha et al., 2006 ; Polyakova et al., 2015 ), and eating disorders (Nakazato et al., 2009 ; Yamada et al., 2012 ) and increases after treatment for these disorders (Nakazato et al., 2009 ; Yamada et al., 2012 ; Yoshimura et al., 2007 ). Plasma and serum BDNF have been identified as indicators of stress in both the general population and healthcare workers (Castillo‐Navarrete et al., 2023 ; Håkansson et al., 2017 ; He et al., 2018 ; Okuno et al., 2011 ). A recent study found that higher academic stress is associated with lower peripheral BDNF, with sensitivity to the duration of stress (Castillo‐Navarrete et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma and serum BDNF have been identified as indicators of stress in both the general population and healthcare workers (Castillo‐Navarrete et al., 2023 ; Håkansson et al., 2017 ; He et al., 2018 ; Okuno et al., 2011 ). A recent study found that higher academic stress is associated with lower peripheral BDNF, with sensitivity to the duration of stress (Castillo‐Navarrete et al., 2023 ). Reduced serum BDNF levels have been observed in nurses experiencing insomnia (Furihata et al., 2020 ), and BDNF gene polymorphisms, such as Val66Met and rs6265, have been implicated in moderating occupational distress among Chinese healthcare workers (He et al., 2018 ; Jia et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Higher education epitomizes this stress due to hefty workloads. Concurrently, students often face family separation, job entry, and new environments ( Barraza-Macías, 2007 ; Castillo-Navarrete et al, 2023a ). University students encounter notably stressful periods, requiring significant adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…BDNF is vital for functions like dendritic branching, spine morphology, synaptic plasticity, and long-term potentiation (LTP). Consequently, it affects memory, learning, appetite, and sleep ( Castillo-Navarrete et al, 2023a ; Karege et al, 2002 ; Lommatzsch et al, 2005 ; Nagahara & Tuszynski, 2011 ).…”
Section: Introductionmentioning
confidence: 99%